MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK DENGAN MEMANFAATKAN BAHAN BEKAS DARI TUTUP BOTOL DI TAMAN KANAK-KANAK KASANG PUDAK KECAMATA KUMPEH ULU KABUPATEN MUARO JAMBI - Linda Susianti; Atika Wirdasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of Educational Game Tools (APE) using used bottle caps media and its impact on the cognitive development of early childhood at Taman Kanak-Kanak Kasang Pudak. The main problem underlying this research is the low concentration of children, lack of skills in ordering numbers, and high level of boredom in learning basic mathematics due to learning methods that tend to be abstract and monotonous. The approach used in this study is descriptive qualitative with a case study method. The research subjects consisted of the Principal, classroom teachers, peer teachers, and 5 children of Group B at Taman Kanak-Kanak Kasang Pudak. Data collection techniques were carried out through participatory observation and structured interviews. Data analysis was carried out by examining observation sheet instruments and development records, while data validity was tested using source triangulation. The results showed that the utilization of Educational Game Tools (APE) from used bottle caps consistently proved to be highly effective in shifting children's boredom and providing optimal cognitive stimulation. Children's cognitive development experienced a significant increase, where they are now able to recognize numbers 1 to 10 in a fun way, become more focused, independent in completing tasks, and proficient in performing simple addition and subtraction operations through concrete object manipulation. In conclusion, habituation through concrete used goods learning media can effectively shape children's logical thinking from an early age.